MODEL KEBIJAKAN PENGEMBANGAN DAYAH BERBASIS DIGITAL DI AL-MUSLIMUN ISLAMIC BOARDING SCHOOL - Safitri, Revi; Dedek Dhea Fitriana; Suhaila (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2024)
Digital-based dayah development is an innovation in Islamic education that combines religious knowledge and technological knowledge to support santri learning activities in making changes and utilizing the opportunities of today's digital world. This research uses descriptive qualitative research using field research techniques. The informants used were the principal and several ustaz who acted as accreditation coordinators. From the results of the discussion, it explains that the development of digital-based dayah also provides added value for santri, namely they can understand a new educational thing by combining religious education values with technological innovation. The conclusion can be drawn that the development of digital-based dayah has a significant role in improving the quality of education and learning of santri, through the application of technology in education, such as digital learning and computer-based examinations, dayah can expand access and increase the effectiveness of learning